Old World Vultures Reflect Effects of Environmental Pollutants Through Human Encroachment. (8th June 2022) - Krüger, Sonja C.; Botha, Andre; Bowerman, William; Coverdale, Brent; Gore, Meredith L.; van den Heever, Linda; Shaffer, L. Jen; Smit‐Robinson, Hanneline; Thompson, Lindy J.; Ottinger, Mary Ann
Abstract: African wildlife face challenges from many stressors including current and emerging contaminants, habitat and resource loss, poaching, intentional and unintentional poisoning, and climate‐related environmental change. The plight of African vultures exemplifies these challenges due to environmental contaminants and other stressors acting on individuals and populations that are already threatened or endangered. Many of these threats emanate from increasing human population size and settlement density, habitat loss from changing land use for agriculture, residential areas, and industry, and climate‐related changes in resource availability. Environmental chemicals that are hazardous include legacy chemicals, emerging chemicals of concern, and high‐volume‐use chemicals that are employed as weed killers and in other agricultural applications. Furthermore, there are differences in risk for species living in close proximity to humans or in areas affected by habitat loss, climate, and industry. Monitoring programs are essential to track the status of nesting pairs, offspring survival, longevity, and lifetime productivity. This is important for long‐lived birds, such as vultures, that may be especially vulnerable to chronic exposure to chemicals as obligate scavengers. Furthermore, their position in the food web may increase risk due to biomagnification of chemicals. We review the primary chemical hazards to Old World vultures and the interacting stressors affecting these and other birds. Habitat is a major consideration for vultures, with tree‐nesters and cliff‐nesters potentially experiencing different risks of exposure to environmental chemicals. The present review provides information from long‐term monitoring programs and discusses a range of these threats and their effects on vulture populations. Environ Toxicol Chem 2022;41:1586–1603. © 2022 SETAC